Estrategias de marketing online de la Veterinaria Zurivet de la ciudad de Babahoyo periodo 2022. - Chavez Pérez, Stefanie Dayanna (2023)
This case study seeks to determine the online marketing strategies of VETERINARIA ZURIVET, which it uses through social networks to present information to customers who use the service provided by VETERINARIA ZURIVET. A descriptive investigation was applied while for the collection of information the customer survey will be carried out. The objective of the case study is to analyze online strategies through a situational diagnosis at VETERINARIA ZURIVET, with the purpose of inquiring about the efficiency of the commercial establishment in terms of carrying out actions that help increase the profitability of the business and better positioning in the local market. The documentary method that allowed obtaining information from secondary sources such as books, magazines, scientific articles, web pages was also applied. Likewise, the inductive method was used with which general conclusions were reached from specific premises obtained from the corresponding information. The technique applied was the interview with the owner of the veterinary to gather information about the problem. The results of the investigation allowed to know that in the commercial establishment there are a series of problems that affect its growth, such as: weak administration, lack of application of Online strategies and strategic marketing, in addition it does not have automation of sales processes, the importance of digital tools to increase sales, among other problematic situations and also that there is a need to implement online marketing strategies.